Techno-economic analysis of a novel laccase production process utilizing perennial biomass and the aqueous phase of bio-oil - Elmin Rahic; Nicholas Cassady; Kurt Rosentrater (Bioresources and Bioprocessing)
Abstract This study explored a novel laccase production process utilizing perennial biomass and the aqueous phase from bio-oil. Experimental and techno-economic modeling were coupled to gain insight into and optimize the solid-state fermentation conditions for minimizing the laccase selling price. At relatively small scales, processing only 230 Mg of prairie biomass per year, a 5-year return on investment required a minimum laccase selling price of $0.05/kU, assuming a 10% discount rate. The associated sensitivity analysis showed the minimum laccase selling price to be most sensitive to parameters affecting laccase output from the plant, which included the number of batches produced per year and laccase recovery assumptions. Limitations and future outlooks were provided, emphasizing the need for further process optimization to minimize fermentation time and downstream losses.